Правові засади статусу спеціальних державних органів в Україні - Мельниченко, В.І.; Плахотнюк, Н.Г. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Освещается вопрос определения статуса таких специальных государственных органов, как Фонд государственного имущества, Антимонопольный комитет, а также правоохранительных органов. Автор относит эти органы к центральным органам исполнительной власти со специальным статусом. The article is devoted the question of determination of status of such special public organs as pund of state property, Antimonopoly committee, and also law enforcement authorities. The norms of Constitution and Law of Ukraine «About Cabinet Ukraine» ground to attribute these organs to the central organs of executive power with the special status.